POSITIVE TEACHER LANGUAGE: IMPROVING TEACHER-STUDENT RELATIONSHIPS AND ENGAGING LOW PROGRESS STUDENTS (Proceedings of International Conference on Special Education, 2023)
Teacher’s language can help create a supportive and conducive classroom environment for learning. Positive Teacher Language (PTL) is one of ten practices in the Responsive Classroom approach. PTL emphasizes the careful and conscientious use of words, voice, tone, and pacing by the teacher when talking to students, and together with effective listening skills, will nurture students to develop self-discipline, build sense of belonging, and encourage students to learn and achieve in an engaging and active way. While research has shown that a strong teacher-student relationship is critical as a firm foundation for learning for low progress students, there are few research studies in the Singapore context that look at the how-to of building teacher-student relationships. The purpose of this research study was to evaluate the impact of a teacher professional development program on PTL to improve teacher-student relationships and to engage low progress students. We utilized a single-case research design, specifically, the multiple baseline across participants design. Twelve teachers and 18 students from two primary schools participated in the study. The outcome measures were direct classroom observation of students’ classroom engagement and audio-recording of lessons to collect data on teachers’ use of PTL. Teachers completed a questionnaire and were interviewed on their views on the acceptability and effectiveness of PTL. Teachers reported high acceptability of the PTL intervention, and they perceived that PTL is effective and beneficial for their students. However, the results revealed that the task of unlearning formed teacher talk habits and learning the new PTL presented a steep learning curve for the teachers. Performance feedback to the teachers led to greater use of PTL in the classroom. However, this study did not show conclusive findings with regards to the effect of PTL on students’ classroom engagement and teacher-student relationships.